Complex Airway Management in Patients with Tracheal Cartilaginous Sleeves. (16th June 2021) - Noble, Anisha R.; Cunningham, Michael L.; Lam, Austin; Wenger, Tara L.; Sie, Kathleen C.; Perkins, Jonathan A.; Dahl, John P.
Abstract : Objectives/Hypothesis: A tracheal cartilaginous sleeve (TCS) is a rare anomaly characterized by anterior fusion of tracheal cartilages. TCS is associated with syndromic craniosynostoses including Apert, Crouzon and Pfeiffer syndromes and FGFR2, FGFR3, and TWIST1 variants. This study presents a 30‐year review of patients with syndromic craniosynostosis and TCS and describes diagnostic methods, genetic variants, surgical interventions, and long‐term outcomes. Study Design: Retrospective, single‐institution review. Methods: This review included patients with syndromic craniosynostosis and TCS treated at Seattle Children's Hospital from 1990 to 2020. Tracheostomy, genetic variants, and additional surgery were primary measures. Fisher's exact test compared need for tracheostomy in patients with proposed high‐risk ( FGFR2 p.W290 or FGFR2 p.C342) versus low‐risk genetic variants. Results: Thirty patients with TCS were identified. Average age at diagnosis was 12 months (range 2‐weeks to 7.9‐years; standard deviation 19.8 months). Syndromes included Pfeiffer (37%), Apert (37%), and Crouzon (26%). Severe obstructive sleep apnea was present in 76% of patients. Tracheostomy was performed in 17 patients (57%); five were successfully decannulated. Additional interventions included adenotonsillectomy (57%), nasal (20%), laryngeal (17%), and craniofacial skeletal surgery (87%). All patients with Pfeiffer syndrome and FGFR2 p.W290C variants and 83% of patients with FGFR2 p.C342 variants required tracheostomy, differing from other variants ( P  = .02, odds ratio 33, 95% confidence interval 1.56–697.96). One patient (3%) died. Conclusion: TCS contributes to multilevel airway obstruction in patients with syndromic craniosynostosis. Genetic testing in patients with FGFR2 ‐related syndromic craniosynostoses may identify those at risk of TCS and facilitate early intervention. A better understanding of this patient population may foster individualized airway management strategies and improve outcomes. Level of Evidence: 4 Laryngoscope, 132:215–221, 2022